The transcription factor PHR1 plays a key role in the regulation of sulfate shoot-to-root flux upon phosphate starvation in Arabidopsis - Rouached, Hatem (BioMed Central, 2011)
BACKGROUND: Sulfate and phosphate are both vital macronutrients required for plant growth and development. Despite evidence for interaction between sulfate and phosphate homeostasis, no transcriptional factor has yet been identified in higher plants that affects, at the gene expression and physiological levels, the response to both elements. This work was aimed at examining whether PHR1, a transcription factor previously shown to participate in the regulation of genes involved in phosphate homeostasis, also contributed to the regulation and activity of genes involved in sulfate inter-organ transport. RESULTS: Among the genes implicated in sulfate transport in Arabidopsis thaliana, SULTR1;3 and SULTR3;4 showed up-regulation of transcripts in plants grown under phosphate-deficient conditions. The promoter of SULTR1;3 contains a motif that is potentially recognizable by PHR1. Using the phr1 mutant, we showed that SULTR1;3 up-regulation following phosphate deficiency was dependent on PHR1. Furthermore, transcript up-regulation was found in phosphate-deficient shoots of the phr1 mutant for SULTR2;1 and SULTR3;4, indicating that PHR1 played both a positive and negative role on the expression of genes encoding sulfate transporters. Importantly, both phr1 and sultr1;3 mutants displayed a reduction in their sulfate shoot-to-root transfer capacity compared to wild-type plants under phosphate-deficient conditions. CONCLUSIONS: This study reveals that PHR1 plays an important role in sulfate inter-organ transport, in particular on the regulation of the SULTR1;3 gene and its impact on shoot-to-root sulfate transport in phosphate-deficient plants. PHR1 thus contributes to the homeostasis of both sulfate and phosphate in plants under phosphate deficiency. Such a function is also conserved in Chlamydomonas reinhardtii via the PHR1 ortholog PSR1.